Clinical and Functional Outcome of Meniscal Injuries Treated with Platelet-Rich Plasma: A Single-Center Case Series - Medina-Porqueres, Iván; Martin-Garcia, Pablo; Sanz-De-Diego, Sofia; Gómez-Cáceres, Abel; Moya-Torrecilla, Francisco; Reyes-Eldblom, Marcelo; Rosado-Velazquez, Daniel (IOAP-MPDI, 2022)
Meniscal injuries are among the most frequently encountered conditions in the knee joint. Therapeutic approaches are diverse and are largely dependent on the extent and location of the injury. The purpose of this study was to describe the clinical and functional outcomes of an intraarticular and percutaneous platelet-rich plasma (PRP) injection regime in patients with stable meniscal injuries. Demographics, the type of tear, affected knee, surgical procedure, type of intervention, follow-up period, and outcomes were recorded in all cases. Patient-reported outcome measures included the Knee Injury and Osteoarthritis Outcome Score (KOOS) and Tegner activity level scale. Overall patient satisfaction, quality of life, and pain intensity were also assessed. A total of 38 cases (8 females) had sustained a stable meniscal lesion (32 medial, 6 lateral) and met the inclusion criteria. All of them received three intraarticular and percutaneous PRP injections. Patients receiving the PRP injection regime reported clinically (p = 0.000) and functionally (p = 0.000 and p = 0.001) significant improvement in all outcome measures during this interval. All patients reported they were very satisfied or satisfied with the outcome. The results of this study suggest that the treatment of stable meniscal injuries with percutaneous–intraarticular PRP injections can achieve a significant clinical and functional improvement.
Keywords: Meniscos-Heridas y lesiones; Meniscus injury; Growth factors; Perimeniscal; knee